Evaluation of potential side activities of commercial enzyme preparations used in winemaking. (13th February 2014) - Fia, Giovanna; Canuti, Valentina; Rosi, Iolanda
Summary Twenty‐one commercial enzyme preparations used in winemaking were characterised for the α‐L‐rhamnosidase, α‐L‐arabinosidase, β‐D‐xylosidase, β‐D‐galactosidase, β‐D‐glucosidase, esterase, protease, cinnamoyl esterase and laccase activities. A new rapid fluorimetric method to assay esterase activity was developed. Enzyme preparations differed for the level of each enzyme activity assayed rather than for the type of enzymatic activity detected. High levels of protease, glycosidase, esterase and cinnamoyl esterase activity were found among enzyme preparations for different technological applications. A drastic reduction in the level of cinnamoyl esterase was observed in commercial grape juice, pH 3.6, total acidity 5.3 g L−1, sugar 170 g L−1. Protease activity was only weakly reduced, from 10 to 20%, in commercial grape juice. β‐glucosidase activity levels are reduced in the presence of increasing concentration of glucose but are still present at the higher glucose concentration (100 g L−1). The extent of the reduction observed was dependent on the enzymatic preparations tested.